The Role of Informality in Shaping Economic Policy Integration - Elgin, Ceyhun (Revue Interventions économiques / Papers in Political Economy, 2026)
This paper examines the relationship between trade linkages, disconnects, and informality in shaping economic policy integration. As global trade undergoes significant transformations due to systemic shocks and structural changes, the informal economy emerges as a crucial yet often overlooked factor in trade policy formulation and analysis. The paper argues that the informal sector plays a critical role in both creating trade disconnects and catalyzing new trade linkages, challenging traditional approaches to trade governance while opening possibilities for innovative policy solutions. The study begins by establishing a conceptual framework that brings together notions of trade linkages, disconnects, and informality. It then explores how informality acts as a source of trade disconnects complicating data analysis, policy enforcement, and market dynamics. Simultaneously, the paper investigates the potential of informal economies to forge unexpected economic connections, particularly in cross-border trade and the digital economy. Examples from African informal trade networks and e-commerce platforms demonstrate this potential. The research then explores the governance implications of these dynamics, emphasizing the need for more inclusive trade policies that can effectively navigate the realities of economies with large informal sectors. It discusses emerging strategies for policy development, such as greater inclusion of informal sector representatives in trade policy formulation and the use of innovative policy instruments that bridge formal and informal economic structures. By bringing together concepts of trade linkages, disconnects, and informality, this research contributes to a more nuanced understanding of the challenges and opportunities facing trade policymakers in the 21st century. It calls for a rethinking of how to approach trade policy formulation and implementation, advocating for new theoretical frameworks and governance models that can balance the dynamism of informal economies with the need for effective regulation and social protection.